Arah Kebijakan Hukum Politik Ekonomi - Mardalena Hanifah (Jurnal Ilmu Hukum, 2012)
Law and economics are the pillars of development sothat both must be matched and aligned with the inter-ests of the people. Thus the legal policy direction ofeconomic policy should be something that has valuein order for legal purposes can be achieved. Since thelaw was established and developed to regulate howthese laws can regulate business behavior by inves-tors that the economic activities which they have givenprotection by law, to ensure the presence of legal pro-tection will be established a rule of law in the areas ofinvestment in the form of legislation, doctrine, juris-prudence, treaties and other agreements to determinethe political direction of economic policy of the law.